Rapid detection method of bacteria species on diabetic infected foot using E-Nose technology - Muhammad Nur Hadi, Salleh; Mohammad Iqbal, Omar, Assoc. Prof.; Ali Yeon, Md. Shakaff, Prof. Dr.; Amizah, Othman, Dr.; Ammar, Zakaria; Azian Azamimi, Abdullah; Mohd Sadek, Yasin; Saiful Akmal, Yusof (Universiti Sains Malaysia, 2013)
Muhammad Nur Hadi Salleh and his team has won the bronze medal at National Research and Innovation Competition (NRIC) 2012, 17th - 19th July 2012 held at Dewan Utama Pelajar, located at USM Main Campus, Penang, Malaysia.